Optical Interference Coatings Conference (OIC) 2022 2022
DOI: 10.1364/oic.2022.wa.5
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Measurement of Mid-IR Refractive Indices of GaAs/AlGaAs in Thin-Film Multilayers

Abstract: We report a method to measure the refractive index of two or more materials in as-deposited thin-film structures by analysis of FTIR transmittance spectra and extraction of layer thicknesses via SEM, yielding excellent results for a GaAs/AlGaAs DBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The feasibility of the method is verified by an experimental study on a GaAs/Al x Ga 1-x As multilayer [20], which yields results in good agreement with previously-published results and propagated uncertainties on the 10 −4 level in the 2 to 7 µm spectral range. Here, an FTIR spectrometer is used to obtain the photometrically accurate transmittance spectrum and the accurate layer thicknesses are obtained via calibrated SEM metrology.…”
Section: Via X-ray Diffraction (Xrd)supporting
confidence: 80%
See 3 more Smart Citations
“…The feasibility of the method is verified by an experimental study on a GaAs/Al x Ga 1-x As multilayer [20], which yields results in good agreement with previously-published results and propagated uncertainties on the 10 −4 level in the 2 to 7 µm spectral range. Here, an FTIR spectrometer is used to obtain the photometrically accurate transmittance spectrum and the accurate layer thicknesses are obtained via calibrated SEM metrology.…”
Section: Via X-ray Diffraction (Xrd)supporting
confidence: 80%
“…We choose an adequate dispersion model, based on the wavelength region and the material type. In general, we found that models with fewer parameters, such as the model developed by Afromowitz [28] used in our experimental study, are more robust against overfitting to remaining systematic measurement deviations (for details see [20]). However, the model needs to be able to capture expected dispersion variations adequately.…”
mentioning
confidence: 79%
See 2 more Smart Citations